Optimalisasi Pengembangan Batas Dusun sebagai Langkah Kritis dalam Pengelolaan Wilayah Ponteh Galis Pamekasan - Listiana, Heni; Maulidy, Ach. Farid; Eza, Aldo Maulana; Karomah, Dewi; Srikandi, Rayu; Aminah, Siti (Welfare : Jurnal Pengabdian Masyarakat, 2023)
This community service aims to enhance the quality of the environment and the lives of the community in Ponteh Galis Village, Pamekasan, through the installation of village boundary markers. Utilizing the Participatory Action Research (PAR) method involving the community, the research encompasses a preliminary study, socialization, and the installation of village boundary markers. The results indicate that the installation of village boundary markers contributes to resource management, improved environmental quality, and the maintenance of peace within the village while also strengthening community participation in environmental decision-making. This project provides insights into the importance of proper village boundary marker installation in improving the quality of the environment and the lives of the community in Ponteh Galis Village.